Antifungal Activity of the Essential Oil of Echinops kebericho Mesfin: An In Vitro Study - Beressa, Tamirat Bekele; Deyno, Serawit; Alele, Paul E. (Evidence-Based Complementary and Alternative Medicine, 2020)
Background: Echinops kebericho is an endemic medicinal plant in Ethiopia widely used in the treatment of infectious and noninfectious diseases. Essential oils are known for their antibacterial, antifungal, antiviral, insecticidal, and antioxidant properties. +is study evaluated the antifungal activity of essential oil from E. kebericho against four common pathogenic fungi and two standard strains. Methods: +e essential oil was obtained by hydrodistillation. +e antifungal screening was done by agar well diffusion method. Minimal inhibitory concentrations (MICs) were determined by broth microdilution. Minimal fungicidal concentrations (MFCs) were determined by subculturing fungal strains with no visible growth onto a Sabouraud dextrose agar (SDA) plate. Results: Candida albicans and Cryptococcus neoformans were highly sensitive while Aspergillus flavus did not show sensitivity up to 1 mg/ml of essential oil; MICs ranged from 0.083 mg/ml to 0.208 mg/ml. Concentration and fungal species showed significant dose-dependent associations (p < 0.0001) with antifungal activity. +eMICs of essential oil were comparable to those of the standard drug (fluconazole) against C. glabrata and C. krusei. +e lowest MFC of the essential oil was observed against Candida parapsilosis (0.145 mg/ml) while the highest MFC was against Candida krusei (0.667 mg/ml). Conclusion: Echinops kebericho essential oil showed noteworthy antifungal activity against Cryptococcus neoformans, Candida albicans, and Candida glabrata and could be a potential candidate for further antifungal drug development.
Keywords: Echinops kebericho; Medicinal Plants; Infectious and noninfectious diseases.; Essential oils